ANALISIS PENGEMBANGAN KELAPA OLAHAN DI KECAMATAN MAWASANGKA KABUPATEN BUTON TENGAH - Purnamasari, Wa Ode Dian (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2018)
This study aims to analyze the development of processed coconut based on the financial feasibility aspect and additional value of development processed coconut. This study is conducted at Mawasangka subdistrict, Central Buton Regency. In drawing the total of the respondent, it is drawn with the Slovin formula as many 55 respondents from 122. The result of this study shows that the development of processed coconut at Mawasangka subdistrict, Central Buton Regency to copra production business and shell charcoal was declared viable based on financial analysis obtained R/C ratio in amount 1,67 for copra and shell charcoal get value in amount 5,47. the cultivation of coconut to copra and shell charcoal is done for 3-4 times production in a year. Based on the result, it is suggested that the quality and volume of cultivation of processed coconut in the Mawasangka subdistrict highly need to be increased in order to be able to compete in the global market. Promotion of cultivation of processed coconut in the Mawasangka subdistrict also still needs to be increased in order that the market can be more exposed and increase a total of customers to overcome the poor management and limited capital. Keywords: feasibility analysis, processed coconut